2015
DOI: 10.1111/jfpe.12194
|View full text |Cite
|
Sign up to set email alerts
|

Variable Retort Temperature Profiles for Canned Papaya Puree

Abstract: Constant retort temperature (CRT) processes for thermally treated foods are usually time-consuming and have drastic impact on food quality. Variable retort temperature (VRT) processes may decrease the processing time and may retain better the food nutritional quality. Five isolethal profiles (one CRT and four VRT) for preparing papaya puree (pH 3.8) were designed using pectin methyl esterase as the target enzyme for thermal processing, and their effect on the puree quality was evaluated. The objective was to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 25 publications
0
3
0
2
Order By: Relevance
“…The VRTP is a powerful tool that can be utilized to reduce processing time, maximize quality retention, and, more importantly, reduce the furan formation in foods to the recommended values. Other authors [ 25 ] have shown that applying a VRTP during pasteurization of canned papaya pure was possible to reduce the processing time 33% compared with CRTP; these findings implied that the retention of vitamin C was notably increased from 19% for a CRTP to 46% for a VRTP, which clearly showed an improvement in quality retention applying this optimization.…”
Section: Variable Retort Temperature Profiles V/s Constant Retort Temperature Profiles: De-signing Processes To Delay Precursors Releasementioning
confidence: 80%
See 1 more Smart Citation
“…The VRTP is a powerful tool that can be utilized to reduce processing time, maximize quality retention, and, more importantly, reduce the furan formation in foods to the recommended values. Other authors [ 25 ] have shown that applying a VRTP during pasteurization of canned papaya pure was possible to reduce the processing time 33% compared with CRTP; these findings implied that the retention of vitamin C was notably increased from 19% for a CRTP to 46% for a VRTP, which clearly showed an improvement in quality retention applying this optimization.…”
Section: Variable Retort Temperature Profiles V/s Constant Retort Temperature Profiles: De-signing Processes To Delay Precursors Releasementioning
confidence: 80%
“…Then, a process performed under variable retort temperature profiles (VRTPs) conditions might be an interesting and better alternative compared to the classic CRTPs process. Variable retort temperature profiles mode is based on the optimal temperature control of the retort, allowing the generation of positive and negative temperature ramps [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ]. The VRTP has been applied and studied as a tool to improve quality retention, but the paramount factor of the application is related to the reduction in processing time [ 18 , 19 , 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…En su estudio, Emelike & Ebere (2015) encontraron una reducción significativa de vitamina C en el jugo de anacardo (48 mg/100 ml) pasteurizado a 80 °C. Además, Avila-Gaxiola et al (2016) hallaron, a través del procesamiento de temperatura de retorta constante, que la retención de la vitamina C en puré de papaya en conserva fue de 65.71%.…”
Section: Estabilidad De Vitamina Cunclassified
“…Se desconocen trabajos enfocados en la retención de vitamina C durante el procesamiento de enlatado de la pulpa de copoazú o del género Theobroma, a pesar de que la literatura muestra publicaciones disímiles en diferentes periodos. De ellas, al 2021, según la base de datos de Web of Science, se publicaron trabajos de Das Neves Selis et al, 2021;De Oliveira et al, 2021;Silva et al, 2021;Tenea & Ortega, 2021. No obstante, existen antecedentes de que se ha evaluado la retención de vitamina C en frutas como naranja (Maeda & Mussa, 1986), mango (Ahmed et al, 2005), manzana anacardo (Emelike & Ebere, 2015), papaya (Avila-Gaxiola et al, 2016) y albaricoque (Adkison et al, 2018). A partir de este panorama, se planteó la siguiente hipótesis: el procesamiento adecuado de la pulpa de copoazú enlatado garantiza el uso comercial en empresas agroindustriales, además de permitir la reducción óptima de la vitamina C.…”
Section: Introductionunclassified
“…Ansorena and Salvadori ( 13 ) found that the thiamine retention value of canned mussels treated with variable temperature (with 9 temperature stages between 110 and 140°C) was higher than that treated with constant temperature (134–137°C). Avila−Gaxiola et al ( 14 ) determined a suitable processing temperature (75°C/19.0 min, 80°C/8.5 min, 90°C/10.7 min and 6°C/20.8 min) based on the vitamin C content, consistency index and color of canned papaya puree. In contrast to general retort heating, variable temperature heating is equivalent to stepwise retort heating, which can reduce the temperature difference between the food surface and the inside.…”
Section: Introductionmentioning
confidence: 99%